Revue Des Doses D’exposition Et De La Justification Des Radiographies Standard En Pratique Pédiatrique Au Togo - Tchaou, M.; Gnakadja, G.N.; N’timon, B.; Sonhaye, L.; Amadou, A.; Dansou, M.; Agoda-Koussema, L.K.; Adjenou, K.; N’dakena, K. (European Scientific Journal, ESJ, 2016)
Aims: To assess the justification of indications and exposure doses to children during radiographics. Methods: Prospective study of 102 X-ray exams of children collected over a period of 6 months in the Department of Radiology of Kara Teaching Hospital. Objectives: To assess the rationale guidance and exposure doses to children when standard radiographic examinations. Methodology: prospective observational study of 102 standard radiographs (Rx) collected in the radiology department of the University Hospital of Kara on a 6 month period. Results: Male children were predominant with a sex ratio boy / girl of 1.3. The predominant age group was the 5 to 10 years. Chest X-rays were the most practiced exam, with 43%. According to the Guide of well practices of French Society of Radiology (SFR) and the French Society of Biophysics and Nuclear Medicine (SFBMN), 80% of exams were justified. The comparison of our results to diagnostic reference levels (DRLs) shows that 43% and 39% of standard X-rays had dosimetric values exceeds the RDLs respectively the entrance Dose (De) and Dose Surface Product (DSP). Conclusion:Our study reveals that compliance guidance assessments to the proper use of medical imaging examinations guide was not always effective but satisfactory. The study dosimetric constants showed that the dose to children exceeded in a large proportion of the French and Belgian DRLs.